In-vitro antioxidant, antidiabetic, anticholinergic activity of iron/copper nanoparticles synthesized using Strobilanthes cordifolia leaf extract - Dharmalingam Kirubakaran; Kuppusamy Selvam; Palanisamy Prakash; Muthugounder Subaramanian Shivakumar; Manickam Rajkumar (Elsevier, 2023)
The Strobilanthes cordifolia plant, a member of the Acanthaceae family, has been extensively studied due to its wide range of biological properties. This particular research focused on the green synthesis of FeNPs/CuNPs and evaluated the effectiveness of the experiment through various characterization techniques, including UV, FTIR, XRD, and SEM with EDAX. The UV analysis provided valuable insights, showing that the synthesized nanoparticles had the highest absorption values at 462nm for FeNPs and 438nm for CuNPs. FTIR analysis confirmed the presence of different functional groups, while XRD measurements validated their crystalline nature. SEM data revealed the diverse shapes of the nanoparticles, including rods and spherical shapes. Additionally, EDAX analysis confirmed the presence of Fe and Cu elements in the biosynthesized nanoparticles. The antibacterial activity of FeNPs and CuNPs against Staphylococcus aureus and Escherichia coli showed significant inhibition. Moreover, the nanoparticles demonstrated strong antioxidant activity, as evidenced by their effective inhibition in DPPH and ABTS assays. Their potential as anti-diabetic agents was also explored, with assessments of their inhibitory effects on α-Amylase and α-Glucosidase enzymes. Additionally, the nanoparticles displayed inhibitory effects on anti-cholinergic enzymes such as AChE and BChE. Furthermore, comprehensive toxicological studies revealed a higher level of mosquito larvicidal activity against Aedes aegypti, Anopheles stephensi, and Culex quinquefasciatus. Among these, the FeNPs exhibited a larval mortality rate of 95% in Cx. Quinquefasciatus, while the CuNPs showed a rate of 93%. In conclusion, this study demonstrated that FeNPs/CuNPs possess favorable characteristics and significant potential for various biomedical applications.